Graves’ disease does not pose an increased risk of thyroid cancer (Annals of Medical Research, 2021)
Aim: The information on increased cancer risk in thyroid nodules in the background of Graves’ disease (GD) is rarely published. In GD, thyroid stimulating hormone (TSH) and TSH receptor antibody (TRAB) are held responsible for playing the key role in the enlargement of nodules and carcinogenesis. In this study, our aim was to evaluate the relationship between GD and thyroid nodules and whether GD increases the risk of thyroid cancer.Material and Methods: TAll patients diagnosed with GD were evaluated for TRAB, anti-thyroidperoxidase (anti-TPO), anti-thyroglobulin (anti-TG), and with thyroid function tests (TSH, sT3, sT4), and thyroid ultrasonography. Fine needle aspiration (FNA) biopsy was performed on the suitable thyroid nodules.Results: Archived records of 182 cases followed-up with the diagnosis of GD between 2008-2014 were evaluated retrospectively. Thyroid nodules were found in 38% (n=69) of the cases. The results of the FNA biopsy of 22 of the 26 (30.5%) nodules of a total of 85 nodules were benign, and 4 were indeterminate. Thyroidectomy was performed on 4 cases with indeterminate results and their pathology results revealed that the nodules were benign. In one case operated due to unresponsiveness to medical treatment, papillary thyroid carcinoma (PTC) was detected. No correlation was detected between TRAB positivity and nodule presence and nodule cytology. Conclusion: In the background of GD, increased nodule prevalence, increased cancer risk in nodules, and the concern for poor prognosis, which have been a matter of debate in the recent years, were not confirmed in our study. We recommend the conventional approach to thyroid nodules in the background of GD.
Keywords: Graves’ disease; thyroid carcinoma; thyroid nodule.